Poor prognosis of child and adolescent musculoskeletal pain: a systematic literature review - Michael Skovdal Rathleff; Jens Lykkegaard Olesen; Martin Bach Jensen; Negar Pourbordbari; Allan Riis (BMJ Open)
Objectives To identify baseline patient characteristics that are (1) associated with a poor outcome on follow-up regardless of which treatment was provided (prognosis) or (2) associated with a successful outcome to a specific treatment (treatment effect modifiers).Design Systematic literature review according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines.Data sources Medline, Embase, Cinahl, Web of Science, Cochrane, SportDiscus, OT Seeker and PsychInfo were searched for prospective cohort studies up to February 2019 without limitation in publication date.Eligibility criteria Prospective cohort studies reporting either prognostic factors or treatment effect modifiers on persistent musculoskeletal pain in 0-year-old to 19-year-old children and adolescents. Pain caused by tumours, fractures, infections, systemic and neurological conditions were excluded.Outcome measures Our primary outcome was musculoskeletal pain at follow-up and identification of any baseline characteristics that were associated with this outcome (prognostic factors). No secondary outcomes were declared.Method Two reviewers independently screened abstracts and titles. We included prospective cohort studies investigating the prognosis or treatment effect modifiers of 0-year-old to 19-year-old children and adolescents with self-reported musculoskeletal pain. Risk of bias assessment was conducted with the Quality in Prognostic Studies tool.Results Twenty-six studies yielding a total of 111 unique prognostic factors were included. Female sex and psychological symptoms were the most frequent investigated prognostic factors. Increasing age, generalised pain, longer pain duration and smoking were other identified prognostic factors. No treatment effect modifiers were identified.Conclusion Several prognostic factors are associated with a poor prognosis in children and adolescents with musculoskeletal pain. These prognostic factors may help guide clinical practice and shared decision-making. None of the included studies was conducted within a general practice setting which highlights an area in need of research.PROSPERO registration number CRD42016041378.